Capsule Endoscopy : A Guide to Becoming an Efficient and Effective Reader - Hass, David J. (Springer International Publishing : Imprint: Springer, 2017)
This volume provides a comprehensive introduction and review of small bowel capsule endoscopy (SBCE). The book reviews the data regarding appropriate indications and contraindications for the implementation of small bowel capsule endoscopy, while discussing in detail the evolving role of SBCE in the treatment of obscure gastrointestinal bleeding, and the management of inflammatory bowel disease, small bowel polyposis syndromes, and refractory malabsorption. Topics such as complications of SBCE, methods to perform SBCE on patients with dysphagia or gastric emptying pathology, and understanding the normal anatomy of the gastrointestinal tract when viewed via SBCE are also discussed. In addition, an introduction to colon capsule technology and the next generation of small bowel capsule imaging is reviewed. The text is complemented by several illustrative cases that are demonstrated with both online full length videos as well as an online interactive companion that includes review questions to reinforce concepts learned in the text. Written by experts in the field, Capsule Endoscopy: A Guide to Becoming an Efficient and Effective Reader is an invaluable resource for novice capsule endoscopy readers, fellows in gastroenterology and hepatology, researchers, mid-level providers, residents, and medical students with an interest in learning how to implement and perform SBCE in the investigation of small bowel diseases. .
Keywords: Medicine.; Gastroenterology.; Hepatology.; elektronické knihy; electronic books